Lake‐Atmosphere Heat Flux Dynamics of a Thermokarst Lake in Arctic Siberia. Issue 10 (31st May 2018) - Franz, D.; Mammarella, I.; Boike, J.; Kirillin, G.; Vesala, T.; Bornemann, N.; Larmanou, E.; Langer, M.; Sachs, T.
Abstract: We conducted eddy covariance measurements from April to August 2014 on a Siberian thermokarst lake. The study site is located in the Lena River Delta and characterized as a floating ice lake. Heat fluxes differed in magnitudes, directions and temporal patterns depending on the lake surface conditions ("frozen" ice cover, ice cover melt, and open water). Significant heat release during frozen ice cover conditions highlighted the importance of lakes for the landscape heat budget and water balance. The energy balance was nearly closed during the open water period and highlighted the impact of melting energy on its closure during the ice cover period. Sensible and latent heat dynamics were driven by temperature and water vapor gradients scaled by wind speed, respectively. We calculated bulk aerodynamics transfer coefficients and evaluated the performance of the derived in situ and three independent heat flux parameterization schemes. We found that bulk transfer models perform moderately to poorly for the different lake surface conditions. During the open water period small‐scale temporal variability could not be represented by the models, particularly in case of latent heat flux. The model results were less sensitive to the specific model type than to the accuracy of the surface water temperature measurement, which is dependent on a well‐thought‐out measurement design. Our study stresses considerations that are crucial for similar campaigns in the future, in order to face the measurement challenges encountered on arctic lakes especially during the ice cover period. Key Points: Turbulent heat fluxes were measured (eddy covariance) and parameterized for an arctic thermokarst lake, for distinct lake surface conditions Heat flux magnitudes, directions, and temporal patterns depend on the lake surface conditions (ice, ice melt, and open water) In situ and independent bulk transfer models yield a moderate to weak reproduction of measured heat fluxes with similar performance